Subcritical solvent extraction of total anthocyanins from dried purple waxy corn: Influence of process conditions - Rattana Muangrat (2018)
© 2017 Wiley Periodicals, Inc. Total anthocyanin content in different dried parts of purple waxy corn (Zea mays L. var. ceratina) genotype Fancy Muang 111 was investigated under subcritical solvent extraction. The highest total anthocyanin content of 991.4, 1241.5, and 1552.1 µg cyanidin-3-glucoside per gram dry weight of sample were obtained from dried kernel extraction (water–ethanol at ratio 1:3 as solvent and sample–solvent at ratio 1:20), dried cob extraction (water–ethanol at ratio 1:1 as solvent and sample–solvent at ratio 1:20), dried silk extraction (water–ethanol ratio at 1:1 as solvent and sample–solvent ratio at 1:30), respectively. The extraction was conducted at 100°C for 15 min with N 2 purging. Additionally, the antioxidant activities assessed by 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), and ferric reducing antioxidant power (FRAP) assays showed that the dried silk extract exhibited the greatest antioxidant activity in DPPH assay (IC50 = 3.2 mg/mL), ABTS assay (IC50 = 1.3 mg/mL), and FRAP assay (634.8 mmol FeSO 4 /100 g dry weight of sample). The extract powder had the total anthocyanin content of 632.8 µg cyanidin-3-glucoside/g powder. Practical applications: The anthocyanin extraction from different dried parts of purple waxy corn was investigated by subcritical solvent extraction method. The effect of different parameters such as weight ratio of purple waxy corn samples to water, extraction temperature, extraction time, water-to-ethanol ratio as solvent, and oxygen in the subcritical solvent extraction provided high total anthocyanin content in the extraction, and the dried silk extract containing the highest total anthocyanin content exhibited the greatest antioxidant activity. Therefore, subcritical solvent extraction of total anthocyanins from purple waxy corn has been shown to be feasible and could be applicable in food processing industries. The total anthocyanin extract obtained has the potential to be developed into new health foods and to be used for the production of value-added products.